Interaktionen mellan det balanserade styrkortet och intern kontroll inom Luleå kommun - Wikström, Veronica; Brandt, Monika (2012)
There are many municipalities in Sweden and they are politically controlled organizations with many different activities that should interact. It is increasingly common for the municipalities to work with a balanced scorecard to control the activities. The balanced scorecard steer the organisations from different perspectives. All those perspectives should be in balance. Internal control is a function that will ensure that the municipality follows laws, guidelines, operate effectively and to seem trustworthy to the local citizens. The auditors have pointed out that there is a lack of interaction between the balanced scorecard and internal control within municipalities in Sweden. Our primary purpose, and our research questions is to gain a deeper understanding and identify how the actors look at the balanced scorecard, internal control as well as the interaction between them and the reasons why actors feel that way. We have adopted an actor approach and have made a case study in Luleå municipality, in which the auditors have criticized a lack of interaction between the balanced scorecard and internal control. We have collected empirical data through interviews with actors in Luleå municipality and a municipalityauditor. Theory and literature of the balanced scorecard, internal control and institutional theory has resulted in an analytical model which we have made in support of the empirical analysis of the actors responses. Furthermore, we analyzed the actors opinions and experiences of the interaction between the balanced scorecard and internal control. After the empirical analysis, we have analyzed the data from an institutional perspective. Finally, we conclude that the actors feel that it is good that the balanced scorecard take many different perspectives into consideration, but that there are difficulties with the formulation of the goals. Generally the actors see internal control in a positive way, and that it is a good tool to make the organisation more efficient, to guarantee routines and that the actors ...